IsrÃ¢âilÃ®yÃ¢t dalam Penafsiran al-Qurâan - Musyarrofah, Hj (Program Studi Perbandingan Agama, Fakultas Ushuluddin dan Filsafat, Universitas Islam Negeri (UIN) Sunan Ampel Surabaya, 2012)
The dynamic interpretation of Koran never to stagnate since the holy book revealed to The Prophet Muhammad. Various shades of interpretation has been offered by mufassir, both classical and contemporary. Exegetic activity even will not arrive at the final point during the mind still exists in human. Dissatisfaction human with the principles, approaches and results of interpretation is the proof. In the range of a long history, various books have been compiled by those whoâre experts in the particular field of study, so the result of interpretation is colored by areas of their expertise. Commentary which written by historians will be strongly influenced by elements of history. In a work of interpretation usually contains a lot of good stories, both complete with the sanad or just the story alone. as noted, between the inserts of story, one of them from clerics long before the Prophet Muhammad, either these stories come from Jews, Christians, and others. Those stories in the interpretation study known famously as isrÃ¢âilÃ®yÃ¢t.